2007
DOI: 10.5628/rpcd.07.01.68
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação, controlo e monitorização da condição física da selecção portuguesa de voleibol sénior masculina – época de 2004

Abstract: RESUMO O presente estudo teve os seguintes objectivos: (i) ajustar procedimentos de avaliação e controlo da condição física dos voleibolistas (força, potência, velocidade, agilidade, resistência e flexibilidade) a fim de obter dados credíveis e úteis, em laboratório e em testes de terreno; (ii) colaborar na prescrição de programas de treino de preparação física; (iii) monitorizar os resultados da condição física da Selecção Portuguesa de Voleibol e quantificar as alterações em dois momentos de avaliação e (iv)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In Portugal, one of the main red deer populations is located in the northeast of the country (Trás-os-Montes region). Santos (2009) showed that density varied between 2.27 and 4.70 red deer/km 2 , however Carvalho (2011) reported a density decrease to 1.07 -2.87 red deer/ km 2 in the same population. By applying indirect methods (pellet group counts), Torres et al (2012) identified the environmental variables that affect the distribution and occurrence of this population, showing that red deer was found in areas further away from roads, urban settlements, agricultural fields selecting patches with medium ground cover of shrubs and sparse tree cover.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, one of the main red deer populations is located in the northeast of the country (Trás-os-Montes region). Santos (2009) showed that density varied between 2.27 and 4.70 red deer/km 2 , however Carvalho (2011) reported a density decrease to 1.07 -2.87 red deer/ km 2 in the same population. By applying indirect methods (pellet group counts), Torres et al (2012) identified the environmental variables that affect the distribution and occurrence of this population, showing that red deer was found in areas further away from roads, urban settlements, agricultural fields selecting patches with medium ground cover of shrubs and sparse tree cover.…”
Section: Introductionmentioning
confidence: 99%